1984
DOI: 10.1007/bf01712000
|View full text |Cite
|
Sign up to set email alerts
|

Decreased thiosulfate sulfur transferase (rhodanese) in Leber's hereditary optic atrophy

Abstract: In mammals the major portion of cyanide is converted to thiocyanate by the liver enzyme thiosulfate sulfur transferase (TST) (rhodanese). We have found a much reduced activity of this enzyme in liver biopsies from two affected males of a family with Leber's hereditary optic atrophy and in two isolated cases of the same disease, (compared to liver biopsies from controls or liver samples obtained at autopsy). In one of the patients we studied the effect of a 3-day thiosulfate infusion. The urinary excretion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Some biochemical data suggests an inborn error of cyanide metabolism (23,24) concerning the mechanisms of cyanide detoxification. However, the study of the rhodanese enzyme, implied in this metabolic pathway, has not provided conclusive results (3,19,(16)(17)(18). The disease generally manifests acutely or sometimes subacutely with visual loss affecting often both eyes.…”
mentioning
confidence: 99%
“…Some biochemical data suggests an inborn error of cyanide metabolism (23,24) concerning the mechanisms of cyanide detoxification. However, the study of the rhodanese enzyme, implied in this metabolic pathway, has not provided conclusive results (3,19,(16)(17)(18). The disease generally manifests acutely or sometimes subacutely with visual loss affecting often both eyes.…”
mentioning
confidence: 99%
“…Kruithof et al [ 43 ] showed that TST deficiency was strongly related to the pathophysiology of metabolic diseases, including diabetes and obesity. There is some evidence of STRs activity playing a role in several other diseases, such as Lebers Hereditary Optic Disease (LHOD) (TST) [ 44 , 45 ], human gliomas (TST, MPST, CTH) [ 46 ] and in hemodialysis patients (TST) [ 47 ]. Therefore, these enzymes provide challenges in several fields and responding to them could not only improve the understanding of various diseases but may also provide a way to treat them.…”
Section: Resultsmentioning
confidence: 99%
“…The study of liver biopsies of patients showed that TST activity decreases during the disease progression. Indeed, infusion of these patients with thiosulfate does not cause an increase in the urinary concentration of thiocyanate, in contrast to what is observed for healthy individuals [ 52 ]. This suggests that cyanide detoxification is suboptimal in patients with Leber’s disease, probably due to decreased TST activity.…”
Section: The Two Rhd Classes Tst and Mpst (Two Evolutionarily Related...mentioning
confidence: 99%